Prevalence and Risk Factors of Low Back Pain Among Public Health Students in Papua Province - Ilmidin Ilmidin; Petrus Yohanes Ismail Arwimbar; Apriyana Irjayanti; Galio Rudolfo Dian Burdames; Abdul Hanan; Rizal Fikri; Antonius Satrio Wicaksono Dosinaeng (Lambung Mangkurat, 2026)
As one of the Musculoskeletal disorders (MSDs), Low Back Pain (LBP) is the most prevalent case and a serious problem experienced by both developed and developing countries such as Indonesia. This pain is not only felt by adults but also by university students. This study aims to examine the prevalence and risk factors influencing the occurrence of LBP. The research method used a cross-sectional design with binary logistic regression tests. Data collection was carried out through direct measurements and surveys using questionnaires among students of the Public Health Department at Cenderawasih University, Papua Province, Indonesia. The results of this study showed that the prevalence of LBP complaints among students was 74%, and only one variable significantly influenced the occurrence of LBP, which was Gender, with a p-value of 0.019 and an Odds Ratio of 2.201 (95% CI: 1.136-4.263). Other variables such as the way of carrying a bag and the weight of the bag were nearly significant, both receiving a p-value of 0.090, with an Odds ratio of 1.668 for the way of carrying the bag and 1.645 for the weight of the bag. This study is expected to serve as a basis for future research to assess the influence of other variables on the incidence of LBP.